Pengaruh Kapasitas Sumber Daya Pegawai Negeri Sipil, Komitmen Organisasi dan Pemanfaatan Teknologi Informasi Terhadap Penerapan Pengendalian Intern Kas Pada Satuan Kerja Perangkat Daerah (SKPD) di Lingkungan Pemerintah Kota Banda Aceh - Rahmaniar Rahmaniar (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study aims to examine the effect of human resource capacity and organizational commitment on the application of cash internal controls at the Regional Work Unit in the Banda Aceh City Government. The population in this study amounted to 36 SKPD and 108 respondents who were self from the Head of Service / Head of Agency / Head of Office as Budget Leaders and Users, SKPD Financial Administration Officers (PPK-SKPD) who examined payment request documents and made books on each SKPD cash expenditure , Treasurer of expenditure, Treasurer of receipt if there is cash receipt in the SKPD. Because of this research population, the nature of this research is census. The analytical method used in this study is multiple linear regression. The results of this study indicate simultaneously and partially the variable capacity of civil servant resources, organizational commitment and utilization of information technology affect the implementation of internal cash controls